Pelatihan Pemanfaatan Software ChemDraw sebagai Media Pembelajaran Materi Hidrokarbon Bagi Guru di SMK N 1 BP. BR OKU Timur - Diana Novitasari (Jurnal Indonesia Mengabdi, 2021)
ChemDraw Software has been used as a medium for learning hydrocarbon materials in drawing 2D and 3D chemical structures at SMK N 1 BP BR. The purpose of using the learning media is to improve the teacher's ability to draw chemical structures and draw a series of practical tools. In addition, to improve the quality of chemistry teaching so as to facilitate students' understanding of abstract chemistry learning. The stages of service research that have been carried out include: interviews, providing guidance, direct practice, and holding question and answer activities during service activities. After using the ChemDraw software, the teacher's response was enthusiastic and active during the training process, seen from the number of active participants asking the implementing team. The teacher hopes that after the training on the use of ChemDraw software to students, abstract chemistry learning will be more interesting and challenging through direct student involvement in dynamic illustration learning and interactive visuals.